The construction of the education researcher's ethos: The students' perspective - Teresa Yurén; Luis Enrique García; Evelyn Moctezuma Ramírez; Silvia Briseño Agüero; Ana Esther Escalante (Arizona State University, 2018)
Academic bodies (AB) are research groups that were formed in Mexico at the beginning of the present century, within a policy for the development of higher education teachers. The AB are responsible to train researchers in postgraduate courses. We inquire about what postgraduate students in the field of education say about what the teachers who are members of these AB help them to form the researcher ethos. We interviewed 67 postgraduate students in the field of education (43 women and 24 men) from three universities. We follow a qualitative methodology that combines ethnography with grounded theory and we use the software Atlas Ti  to systematize the information.  We find that students consider that it is enough to appropriate ethics (values and patterns of behavior) to act ethically and consider the ethical teacher's mentoring as key in that process. They do not refer to strategies to help them: make decisions regarding conflicting values or norms (moral judgment), judge equity issues (prudential judgement) and assume responsibility for the future of humanity. This reveals that support of AB for the construction of the researcher ethos is insufficient.